2010
DOI: 10.1007/s11270-010-0376-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physicochemical Methods for Treatment of Cu, Pb, Sb, and Zn in Canadian Small Arm Firing Ranges Backstop Soils

Abstract: This paper presents the results of physicochemical treatment on Pb-, Cu-, Sb-, and Zncontaminated Canadian small arm firing range (SAFR) backstop soils in order to evaluate the potential of such methods for remediation of SAFR backstop soils. Remediation target for the treatment assays was to attain the Québec Department of Environment commercial C criterion or more realistically, to reach the soil burial D criterion. Two treatment lines (TL) were evaluated. TL-1, consisting of jig and Wilfley table (WT) treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Total iron amount was analyzed from iron-phenanthroline complex with a spectrophotometer at a fixed wavelength of 508 nm according to the literature (Eaton et al 1995). Total dissolved solid (TDS) of the water sample was determined according to Laporte-Saumure et al (2010). The sample was filtered with a glass fiber filter, and then, the water was evaporated at 180 °C in a porcelain cup of known weight.…”
Section: Methodsmentioning
confidence: 99%
“…Total iron amount was analyzed from iron-phenanthroline complex with a spectrophotometer at a fixed wavelength of 508 nm according to the literature (Eaton et al 1995). Total dissolved solid (TDS) of the water sample was determined according to Laporte-Saumure et al (2010). The sample was filtered with a glass fiber filter, and then, the water was evaporated at 180 °C in a porcelain cup of known weight.…”
Section: Methodsmentioning
confidence: 99%
“…According to Laporte-Saumure et al [175], the gravimetric techniques can be successfully applied to restore soils heavily contaminated by 16,000 to 38,000 mg Pb/kg and 11,500 mg Cu/kg. The application of the Jig and the shaking table to the fractions higher than 53 microns was highly efficient; allowing the removal of more than 92 and 90% Pb and Cu, respectively.…”
Section: Physical Methods For Metal Removalsmentioning
confidence: 99%
“…Several studies have shown that a chemical process applied downstream of physical separation processes can be successfully used to further reduce the concentrations of inorganic contaminants from soils [173,175,183,184]. In fact, the chemical extraction technologies are frequently proposed to remove toxic metals attached to the fine particles of soil.…”
Section: Leaching Processes Developed For the Solubilization Of Metalsmentioning
confidence: 99%
“…The required adjustments to enhance the decontamination of these soils were defined as follows: 20°tilt, feed water flow of 3.5 L min −1 , washing water flow of 8 L min −1 , and feed pulp composition of 20% total solids (w•w −1 ) (Veetil et al, 2014). For a soil highly contaminated by Pb, Zn, Cu, and Sb found in military shooting grounds, the removals ranged from 60% to 96% under a feed water flow of 3.5 L min −1 , a washing water flow of 8 L min −1 , and a pulp comprising 70% total solids (w•w −1 ) (Laporte-Saumure et al, 2010). The research of Bisone et al (2013) focused on the treatment of the 0.125-1 mm fraction of a soil contaminated by slags and foundry residues.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%